Evaluating Higher Education Institutions through Agency and Resources-Capabilities Theories. A Model for Measuring the Perceived Quality of Service - Vargas-hernández, José Guadalupe (Revista Brasileira de Política e Administração da Educação - Periódico científico editado pela ANPAE, 2016)
The objective of this paper is to explain through the agency theory and theory of resources and capacities as is the process of assessment in higher education institutions. The actors that are involved in the decision-making and the use that is giving the resources derived from repeatedly to practices that opportunistic diminishing the value that is given to the evaluation, in addition to the decrease in team work. A model is presented to measure the perception of service quality by students of the Technological Institute of Celaya, as part of the system of quality control, based on the theoretical support of several authors who have developed this topic (SERVQUAL and SERPERF ) an instrument adapted to the student area of the institution called SERQUALITC is generated. The paper presents the areas or departments to assess and the convenient size, the number of items used by size and Likert scale, the validation study instrument is mentioned. Finally, it is presented the model that poses a global vision of quality measurement process including corrective action services that enable continuous improvement.